Content analysis of quick sampler functionality in Logic Pro X: an investigative study of configuration features - Satya, Royys Bagja Rizky; Sukmayadi, Yudi; Riyadi, Lanang (International Journal of Visual and Performing Arts, 2025)
This study investigates the configuration and functional capabilities of the Quick Sampler feature within Logic Pro X, focusing on its application in audio sample processing for music composition. Utilizing a qualitative content analysis approach based on Krippendorff’s methodology, the research systematically examines key components of Quick Sampler, including Synth Mode, Mod Matrix, and Mapping Section, to evaluate their roles in enhancing workflow efficiency and creative flexibility. Data were gathered from direct interface analysis, supported by documentation and user experience reports. The findings reveal that Quick Sampler’s intuitive drag-and-drop interface, combined with flexible sample modes, simplifies the sampling process, while the Mod Matrix facilitates complex modulation routing that expands sound design possibilities. Although the study is descriptive and qualitative, it highlights Quick Sampler’s potential to streamline compositional processes within digital audio workstations. Future research is recommended to quantitatively measure user efficiency and to compare Quick Sampler’s performance with other DAWs, as well as to explore its optimization for specific music genres.